2021
DOI: 10.3389/fnbeh.2021.748563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Buprenorphine on the Memory and Learning Deficit Induced by Methamphetamine Administration in Male Rats

Abstract: Little is known about the effects of methamphetamine (Meth) and buprenorphine (Bup) on memory and learning in rats. The aim of this investigation was to examine the impact of Meth and Bup on memory and learning. Fourteen male Wistar rats weighing 250–300 g were assigned to four groups: Sham, Meth, Bup, and Meth + Bup and were treated for 1 week. Spatial learning and memory, avoidance learning, and locomotion were assessed using the Morris water maze, passive avoidance learning, and open field tests, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Buprenorphine treatment also reduced HIV burdens and inflammatory monocyte levels in the brain 56 , suggesting that continuing migration of HIV-infected monocytes to the brain is required to maintain HIV-NCI. However, since buprenorphine also affects various aspects of behavior 57 , 58 , additional mechanisms may apply. The ability to reverse NCI is consistent with the state of brain neuropathology in PLWH with mild NCI and in our model of mice with EcoHIV NCI.…”
Section: Discussionmentioning
confidence: 99%
“…Buprenorphine treatment also reduced HIV burdens and inflammatory monocyte levels in the brain 56 , suggesting that continuing migration of HIV-infected monocytes to the brain is required to maintain HIV-NCI. However, since buprenorphine also affects various aspects of behavior 57 , 58 , additional mechanisms may apply. The ability to reverse NCI is consistent with the state of brain neuropathology in PLWH with mild NCI and in our model of mice with EcoHIV NCI.…”
Section: Discussionmentioning
confidence: 99%
“…EcoHIV NCI in mice 54 ; possibly through its action on CCL2 expression 38 . This suggests that buprenorphine reverses NCI through inhibition of monocyte migration, however, buprenorphine also has effects within the brain upon various aspects of behavior 55,56 , so the mechanism of buprenorphine action upon EcoHIV NCI remains under study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, clinical investigations have also demonstrated a moderate dose METH enhances learning and memory function, including visuospatial perception and response speed [ 49 ]. There are also claims that preadolescent METH exposure improves the spatial learning of male rats [ 50 , 51 ]. Conversely, some studies demonstrated various effects of different doses of METH on the nervous system [ 1 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%